Blood glucose and uric acid increases the risk of hypertension in elderly - Sofiana, Liena; Khusna, Arfiani Nur; Pradana, Righa (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension is still a big challenge in Indonesia. Survey data shows that Yogyakarta province is included in the top five provinces with the most cases of hypertension with a number of 35.8% above the average of all Indonesia, which is 31.7%. Life style changes such as dietary changes lead to ready-to-eat dishes that contain lots of fat, high protein and salt but are low in dietary fiber, bringing consequences as one of the factors developing degenerative diseases such as hypertension. The purpose of this study was to determine the relationship between blood glucose and uric acid with the incidence of hypertension in the elderly at Posyandu Lansia Kauman Yogyakarta. Methods: The study was observational analytic with cross-sectional design. The population in this study were all elderly people living in the Posyandu Lansia Kauman Yogyakarta with a total of 33 people. The instrument used was a checklist sheet and the instrument used was a tensimeter, glucometer and uric acid test. The data analysis technique used is the Fisher’s test. Results: There was a significant relationship between blood glucose (p=0.023) and uric acid (p=0.036) with an increased risk of hypertension in the elderly in the Posyandu Elderly Kauman Yogyakarta. Conclusions: There is a relationship between blood glucose and uric acid levels with an increased risk of hypertension in the elderly at the Posyandu Lansia Kauman, Yogyakarta.